Keseimbangan antara Profesionalitas dan Kesejahteraan Guru Bahasa Arab dalam Perspektif Maqasidi Qur'ani - Abas, Abu (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research on language education policy aims to formulate language education policies regarding the inequality between professionalism and teacher welfare from the perspective of Qur'anic maqasidi. The research method used in this policy article is qualitative, with a literature study approach. Policy article data is in the form of policy choices from the perspective of Quranic maqasidi, obtained from various sources of articles, the Quran, applicable regulations, scientific journals, and books. The data collection technique is carried out by documentation. The data analysis was done using data reduction, presentation, and conclusion. The research on language education policy results stated that 21 verses of the Qur'an were reduced into four types of "tawāzun" or "balance." Four types of "tawāzun" are explored with the perspective of Qur'anic maqasidi, namely: 1) balance in the market, 2) balance in the hereafter, 3) universal balance, and 4) religious balance. The four types of "tawāzun" are divided into two types of "tawāzun" at the same time according to the dalālah and qarīnah of each verse. Four types of "tawāzun" or "balance" are thus reduced to formulate language education policies to provide a solution to balance the professionalism and welfare of Arabic teachers. 1) Market share; Providing a balance between rights and obligations, giving good and gentle direction, assigning tasks according to the teacher's ability level, keeping promises including honorarium or salary; 2) The Hereafter; the counsel that teaching is a religious command to plant goodness in the world; 3) Universal; provide balanced work and honorarium; 4) Religious system; every step of learning to hold the principles of the Qur'an. Thus, at least the Qur'ani maqasidi can be a reference for better formulation of school/madrasah policies.